Effects of students’ perception of teachers’ ethnic-racial socialization on students’ ethnic identity and mental health in rural China’s schools - Lai, Angel Hor Yan; Lam, Jason K. H.; Yao, Hong; Tsui, Elaine; Leung, Cynthia (Frontiers in Psychology, 2024)
Introduction: Using students in the Liangshan Yi autonomous prefectures of southwestern China (n=585; 13-15 years old), we examined (i) the effects of perceived teachers’ ethnic-racial socialization on the ethnic identity and mental health of depressive and stress symptoms and (ii) the effects of ethnic identity on depressive and stress symptoms in Yi ethnic minority and Han cultural majority youth. Methods: We conducted a cross-sectional survey and used multistage sampling to collect information. Chinese-validated standardized measures were used: the Patient Health Questionaires-9, Children’s Revised Impact of Event Scale-8, Multigroup Ethnic Identity Measure, Cultural Socialization Scale, and Teachers’ Attitude on Adoption of Cultural Diversity Scale. Multigroup confirmatory factor analysis and multigroup modeling were employed. Results: Three key findings were as follows. (i) Multicultural socialization, that is, socialization related to other cultures, and teachers’ diversity positively affect the ethnic identity of both Yi and Han students; however, socialization related to one’s own culture did not exert any effect. (ii) Teachers’ cultural diversity only affected the mental health of Han students, while socialization with other cultures had no mental health effects in either group. (iii) Ethnic identity affects the mental health of Yi indigenous students only. Ethnic identity resolution decreases depressive and stress symptoms and ethnic identity commitment exacerbated depression and stress. Conclusion : The findings underscore the importance of teachers’ multicultural socialization in the ethnic identity development of both Yi ethnic minority and Han majority students. Ethnic identity further serves as a linking variable bridging perceived teachers’ multicultural socialization practices and mental health in Yi ethnic minority students but not among the Han cultural majority youths. Ethnic identity resolution is a psychological resource for positive mental health in ethnic minority Yi students but not for the Han cultural majority. Research, practice, and policy implications are also discussed.